Avian influenza overview September–December 2023 - European Food Safety Authority; European Centre for Disease Prevention and Control; European Union Reference Laboratory for Avian Influenza; Cornelia Adlhoch; Alice Fusaro; José L. Gonzales; Thijs Kuiken; Gražina Mirinavičiūtė; Éric Niqueux; Karl Ståhl; Christoph Staubach; Calogero Terregino; et al. (EFSA Journal, 2023)
Abstract Between 2 September and 1 December 2023, highly pathogenic avian influenza (HPAI) A(H5) outbreaks were reported in domestic (88) and wild (175) birds across 23 countries in Europe. Compared to previous years, the increase in the number of HPAI virus detections in waterfowl has been delayed, possibly due to a later start of the autumn migration of several wild bird species. Common cranes were the most frequently affected species during this reporting period with mortality events being described in several European countries. Most HPAI outbreaks reported in poultry were primary outbreaks following the introduction of the virus by wild birds, with the exception of Hungary, where two clusters involving secondary spread occurred. HPAI viruses identified in Europe belonged to eleven different genotypes, seven of which were new. With regard to mammals, the serological survey conducted in all fur farms in Finland revealed 29 additional serologically positive farms during this reporting period. Wild mammals continued to be affected mostly in the Americas, from where further spread into wild birds and mammals in the Antarctic region was described for the first time. Since the last report and as of 1 December 2023, three fatal and one severe human A(H5N1) infection with clade 2.3.2.1c viruses have been reported by Cambodia, and one A(H9N2) infection was reported from China. No human infections related to the avian influenza detections in animals in fur farms in Finland have been reported, and human infections with avian influenza remain a rare event. The risk of infection with currently circulating avian H5 influenza viruses of clade 2.3.4.4b in Europe remains low for the general population in the EU/EEA. The risk of infection remains low to moderate for occupationally or otherwise exposed people to infected birds or mammals (wild or domesticated); this assessment covers different situations that depend on the level of exposure.